Characterization of Alginate Beads from Biolectric Producing Thermophilic Bacterial Cells - Andriani, Putri; Irdawati, Irdawati (Jurnal Biologi Tropis, 2025)
Cell immobilization is one of the important techniques in biotechnology to increase the stability and viability of microorganisms during the application process. This study aims to characterize the shape, color, size, and number of colonies of beads resulting from the immobilization of four electrogenic thermophilic bacterial isolates (SSA1, SSA8, SSA14, and SSA16) using sodium alginate as a matrix. The immobilization technique was carried out through the ionic gelation method using 0.2 M CaCl₂, with a concentration of 5% sodium alginate. The results showed that all isolates formed beads with round morphology and clear yellowish color indicating the success of the gelation process and no contamination. The diameter of the beads ranged from 3.8 mm to 4.6 mm, with SSA16 having the largest size. The highest number of colonies was found in SSA14 (147 colonies), followed by SSA16 (140), SSA1 (138), and SSA8 (125). There was a positive correlation between the size of the beads and the number of colonies, indicating that isolates with larger matrix space could accommodate more cells without interfering with metabolic activity. These results suggest that SSA14 and SSA16 have the most optimized physical characteristics of beads for application in Microbial Fuel Cell (MFC) systems.